Odpowiedzi

2010-03-02T19:29:22+01:00
A) x + y = 3
x - 2y = 6
x=3-y
3-y-2y=6
3-3y=6
-3y=6-3
-3y=3/(-3)
y=-1
x=3-(-1)
x=4

b) 2x - 3y = -5
-x + 5y = 12
-x=12-5y/*-1
x=-12+5y
2(-12+5y)=12
-24+10y=12
10y=12+24
10y=36/10
y=3,6
x=-12+18
x=6

c) 4x - 2y = 6
3x + 6y = 12
-2y=6-4x/-2
y=-3+2=5
3x=12-6y
3x=12-30
3x=-18
x=-6

d) x - y = 5
3x + 4y = 8
x=5+y
3(5+y)+4y=8
15+3y=8
3y=-7/3
y=-7/3=2,3
x=5+2,3=7,3

e) 3x - 3y + 3 = 0
x + 1,5y - 2 = 0
x=2-1,5y
3(2-1,5y)-3y=0
6-4,5y-3y=0
7,5y=-6/7,5
y=0,8
x=2-1,2
x=0,8


f) 3x - 4y = 14
- 2x + 7y = - 18
3x=14+4y/3
x=4,6-1,3y
-2(4,6-1,3y)+7y=-18
-8+2,6y+7y=-18
9,6y=-18+8
9,6y=-10
y=-1,04
x=4,6+1,4
x=6


x=
6 2 6
Najlepsza Odpowiedź!
2010-03-02T19:57:45+01:00
A)x=3-y
3-y-2y=6-3
-3y=3\(-3)
y=-1
x=3-(-1)=4
b)
c)4x-2y=6
x=4-2y

4(4-2y)-2y=6
x=4-2y

16-8y-2y=6
x=4-2y

-10y=-10\(-10)
y=1
x=4-2*1
x=2
d)x=5+y
3(5+y)=8

x=5+y
15+3y+4y=8
7y=-7\7
y=-1
x=5=(-1)=4
e)3x-3y-3=0\3
x+1,5y-2=0

x=y-1
y-1+1,5y-2=0

2,5y=3\2,5
y=6
x=5

f)3x-4y=14
-2x+7y=-18\(-2)

3x-4y=14
x=9+3,5y

3(9+3,5y)-4y=14
27+10,5y-4y=14
6,5y=-13\6,5
y=-2
x=2

6 4 6